요로결석 환자의 경정맥 요로조영 검사 시 압박 유무에 따른 영상평가 - 김형균(Hyeong-Gyun Kim); 홍동희(Dong-Hee Hong) (방사선기술과학, 2015)
Intravenous urography (IVU) for urolithiasis is a radiologic examination to diagnosis stone in the ureter path using iodine contrast media, which is radioopacity material. The method includes compression on the upper iliac crest. The compression band prevents outlet of the contrast media through the bladder and enables easier movement to upper urinary tract. This usage depends on the policy of a hospital. Therefore, this study aimed to review and compare the characteristic of progress of contrast media either in compression and non-compression. The retrospective image measurement on 60 cases of intravenous pyelography was conducted at a hospital with the identical type and amount of contrast media as well as criteria for testing. Image measurement was limited to 5 minutes clip, which is optimal for progress of contrast media depending on usage of the compression band. Also, anatomical regions were set as following: "RP" is from renal pyramid to renal pelvis, "PL" is from renal pelvis to lumbar three endplate, and "IU" and "IL" for upper and lower parts from both iliac crests. Analysis has been conducted through the statistical method based on Fisher's Exact Test to find if there are differences of distribution with the anatomical regions with compression or no compression. It has been confirmed that there is no statistical significant difference as the video measurement on 30 cases of compression and non-compression group respectively resulted in P value of 0.580 from left and 0.711 from right (both 0.960). Therefore, it has been concluded that application of a compression band on an intravenous pyelography for urolithiasis patient does not meaningfully affect the progress of contrast media. 요로결석으로 인한 경정맥 요로조영 검사는 방사선 비 투과성 물질인 요오드 조영제를 사용하여 요관의 경로에 있는 결석을 진단하는 방사선학적 검사법이다. 그 검사 방법 중 엉덩뼈 능선 상단에 대한 압박으로, 조영제가 방광으로 배출되는 것을 막아, 상부요로의 묘출을 용이하게 하는 압박대 사용 유무는 병원마다 다른 방법을 적용하고 있다. 연구자들은 실험을 통하여 압박 과 압박을 하지 않은 상태에서 조영제 진행의 특이도를 관찰하여 상호 비교하고자 하였다. 본 연구는 조영제의 종류, 용량, 검사진행 기준이 동일한 일 병원에서 실시한 경정맥 요로조영 검사 60 례를 후향적 영상평가 방법으로 실시하였다. 영상평가는 5 분 영상으로 제한하여 압박 유무에 대한 조영제의 해부학적 주행 위치가 용이한 시간대로 하였으며, 콩팥 피라미드에서 콩팥깔때기까지를 "RP", 콩팥깔때기에서 요추 3 번째 종판까지를 "PL", 양쪽 엉덩뼈 능선을 기준으로 상부와 하부를 "IU"와 "IL"으로 해부학적 영역을 설정하였다. 분석방법은 피셔의 정확 검정에 의한 통계적 방법으로 압박과 압박을 하지 않은 상태에서 해부학적 위치의 분포차이가 있는지를 분석하였다. 압박그룹과 압박을 하지 않은 그룹 각 30 례의 영상평가에서 P 값이 왼쪽 0.580, 오른쪽 0.711, 양쪽에서 0.960 등으로 나타나 통계적으로 유의한 분포의 차이가 없음을 확인하였다. 이로서 요로결석 환자의 경 정맥 요로조영 검사 시 압박 대 사용유무는 조영제 진행에 차이를 주지 않는다는 통계적 결론을 얻었다.